A ESPIRITUALIDADE ENQUANTO DIMENSÃO DA CULTURA ORGANIZACIONAL: ESTUDO DE CASO EM UMA INSTITUIÇÃO CONFESSIONAL DE ENSINO - Damião, Wanderson da Silva (2014)
The spirituality practice in the work has been the subject of research even within the administration, because it is related to the efforts and commitment of the employees of an organization, which refers to aspects of organizational management. Spirituality in the workplace may also be associated to aspects of organizational culture, when this practice becomes an organizational value. Rego, Cunha and Souto (2007) emphasize that a work environment that practicing spirituality, develops five dimensions of spirituality like. the community sense in the team, the conditioning of the individual with the organization values, sense of contribution to the community, the joy at work and the opportunity for the inner life. The study aimed to identify the context of a specific organization, if the dimensions of spirituality adopted in the theoretical reference, they manifested in the perception of the organizations employees. For this, it developed a qualitative exploratory study with the method of case study, in a confessional educational institution in ABC Paulista region. Information was collected through interviews for analysis of the organization, as their culture as practice of spirituality in the workplace. It has also developed a documental analysis of the institution and field observations for better search results. It was found that the confessional educational research institution, it is an organization that in its organizational culture, they has documented spirituality values, practiced and perceived by collaborators. It was also found that the dimensions of spirituality addressed in the theoretical reference, features are perceived by collaborators in the organizations reality. There was emphasis on the dimensions of opportunity for the inner life and sense of community in the team. The organizations managers demonstrated in their depositions that are dedicated to the development of these dimensions and the perception of the institutions employees confirm these elements. So, through these two dimensions of spirituality, the other three are the basis for its development in the context of the research institution. This result can characterize elements in religious educational institutions, however, this research obtains its field boundary and demographic. Future researches in different denominational educational institutions and in different regions, can contribute to more comprehensive conclusions.